2012
DOI: 10.1007/s00590-012-1034-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of early bone loss around the prosthesis by administration of anti-osteoporotic agents and influences of collared and non-collared femoral stem prostheses on early periprosthetic bone loss

Abstract: The current study aims to investigate the effect of anti-osteoporotic agents of collared and non-collared femoral stem prostheses on periprosthetic bone mineral density (BMD) after total hip arthroplasty (THA). 80 patients who received THA due to femur neck subcapital fractures were involved. The treatment groups were given fosamax, caltrate D and Xianlinggubao for oral administration, whereas the control groups were only given caltrate D. BMD at the greater trochiter around the femoral stem prosthesis and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…the anabolic recovery, as demonstrated in experimental models and in clinical trials. 79 In vitro studies in ovariectomized rats 80 have demonstrated that pre-surgery treatment with BPs increases the BMd of the cancellous bone and the stability of hydroxyapatite-coated implants. in the dog model, the early administration of BPs had no significant influence on the extent of bone apposition, the extent or thickness of the hydroxyapatite coating, or the cortical or trabecular bone area around the implants.…”
Section: The Use Of Clodronate In Orthopedic Surgerymentioning
confidence: 99%
“…the anabolic recovery, as demonstrated in experimental models and in clinical trials. 79 In vitro studies in ovariectomized rats 80 have demonstrated that pre-surgery treatment with BPs increases the BMd of the cancellous bone and the stability of hydroxyapatite-coated implants. in the dog model, the early administration of BPs had no significant influence on the extent of bone apposition, the extent or thickness of the hydroxyapatite coating, or the cortical or trabecular bone area around the implants.…”
Section: The Use Of Clodronate In Orthopedic Surgerymentioning
confidence: 99%
“…A total of 446 records were excluded by examining their titles and/or abstracts, leaving 40 records for full-text review. Twenty-nine studies were excluded after full-text review: ten because they reported on non-conventional-length (short, long) or non-HA-coated stems ( 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ), eight because they compared collared versus collarless stems with different designs or coatings ( 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ), five because they were letters to the editor, technical notes, or correspondence ( 38 , 39 , 40 , 41 , 42 ), three because they did not report on any outcomes ( 14 , 43 , 44 ), one because it compared hemiarthroplasty versus THA ( 45 ), one because it was a cadaveric study ( 46 ), and one because it was a non-comparative study ( 47 ). A further three articles were excluded because the outcomes of interest were not presented separately for collared versus collarless stems (the authors were contacted at least three times but none responded) ( 4 , 6 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…High BMD supports bone-implant fixation, and there have been several attempts to improve the quality of the primary arthroplasty and to reduce the incidence of failures caused by loss of BMD [ 29 , 30 ]. A large population-based parallel-cohorts study [ 31 ] found that bisphosphonates could decrease the risk of periprosthetic fractures after THA.…”
Section: Discussionmentioning
confidence: 99%